2007
DOI: 10.1016/j.jacc.2007.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Pacemaker for Atrioventricular Conduction Block After Operative Repair of Perimembranous Ventricular Septal Defect

Abstract: Operative AV block and PPM placement occurred in 1.1% of patients in the total group and in 0.8% of patients comparable to those considered for device closure of PMVSD. A PPM placement is more likely in patients with Down syndrome. These data should be considered as devices are developed and in the future when counseling families about options for PMVSD closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 17 publications
(19 reference statements)
3
69
0
4
Order By: Relevance
“…17) However, the disturbance of conduction system, residual ventricular shunt, neurologic injury, and postoperative mortality are still major postoperative complications, especially in infants with malnutrition. [6][7][8][9][10][11] Our current series reported excellent postoperative outcomes using mattress suturing technique: there was no incidence of complete heart block, reoperation for residual VSD and postoperative mortality. Some may argue that the results can be attributed simply to a learning curve of the surgeon but the comparatively good outcomes are encouraging, and the new technique can be an addition to the armamentarium of pediatric cardiac surgeons.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…17) However, the disturbance of conduction system, residual ventricular shunt, neurologic injury, and postoperative mortality are still major postoperative complications, especially in infants with malnutrition. [6][7][8][9][10][11] Our current series reported excellent postoperative outcomes using mattress suturing technique: there was no incidence of complete heart block, reoperation for residual VSD and postoperative mortality. Some may argue that the results can be attributed simply to a learning curve of the surgeon but the comparatively good outcomes are encouraging, and the new technique can be an addition to the armamentarium of pediatric cardiac surgeons.…”
Section: Discussionmentioning
confidence: 60%
“…Although complete heart block occurred in less than 1% after surgical closure of VSD, 18) it still remains a complication especially in patients who develop pulmonary hypertension and right ventricle hypertrophy which make the relationship between the conduction branches and the margin of the defect more intimate. 5,7,8) Right bundle branch block, which may be associated with diastolic dysfunction in late follow-up, remains another common conduction disturbance with a reported prevalence of 20%-62%. 12,19,20,21) Both are unequivocally linked to the surgical maneuvers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested an association between surgical heart block and small size, but these were inadequately powered to provide definitive data (20,21). Siehr et al (22) have demonstrated that patients weighing less than 4 kilograms were at significantly higher risk for surgical AV block.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated incidence of complete AV block is 1% to 5% [30,31], and it is more frequently observed in patients weighing less than 10 kg. Complete AV block also occurs after surgical repair of VSDs [32]. The Amplatzer perimembranous VSD occluder has an asymmetrical form specially designed to deal with this issue.…”
Section: Ventricular Septal Defectmentioning
confidence: 99%